1998
DOI: 10.1016/s0377-1237(17)30599-3
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Hepatic Failure-a Clinical Profile

Abstract: A combined experience of 37 cases ofsubacute hepatic failure encountered in five major gastroenterology centres over a period of ten years is discussed. Majority (65%) were males with average age of 38 years. Maximum (54%) were in 5th decade. Jaundice (100%), abdominal distention (38.7%), swelling feet (64%), fever (54%), abdominal pain (54%), exhaustion (78.3%) were the major presenting features. Jaundice and ascites were present in all cases. Pedal oedema (78.3%), hepatomegaly (54%), splenomegaly (32.4%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 1 publication
3
4
1
Order By: Relevance
“…Hence with renewed interest, we analyzed our cohort of pediatric LOHF in an effort to recognize and understand this clinical entity better. Clinically detectable ascites was seen in 94% of our children with LOHF which is similar to Indian adults with LOHF (97-100%) [1,7]. However, a lower proportion of ascites (62%) in LOHF is reported from West [4].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Hence with renewed interest, we analyzed our cohort of pediatric LOHF in an effort to recognize and understand this clinical entity better. Clinically detectable ascites was seen in 94% of our children with LOHF which is similar to Indian adults with LOHF (97-100%) [1,7]. However, a lower proportion of ascites (62%) in LOHF is reported from West [4].…”
Section: Discussionsupporting
confidence: 65%
“…Advanced HE was infrequent in our study (10%), which is similar to Gimson et al [4] who reported HE in 68% (21% advanced HE). In contrast, HE was reported to be uncommon feature (16-27%) in 2 adults LOHF studies from India [1,7]. None of the patients in our study had clinical evidence of cerebral edema, which is a rare fea-ture in LOHF (8.5%) in contrast to fulminant hepatic failure (66.7%) [4].…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Presentations that evolve more slowly, or subacutely, can be confused with chronic liver disease . These subacute cases have a consistently less favorable outcome with medical care alone than those with the more rapid onset . Although ALF is initially a manifestation of liver injury, it quickly evolves into multiorgan dysfunction and has many clinical manifestations (Figure ).…”
Section: Defining Acute Liver Failurementioning
confidence: 99%